International Conference on Design and Test of Integrated Systems in Nanoscale Technology, 2006. DTIS 2006. 2006
DOI: 10.1109/dtis.2006.1708701
|View full text |Cite
|
Sign up to set email alerts
|

Additivity of capacitive and inductive coupling in submicronic interconnects

Abstract: Abstract-Constant evolution in integrated circuit technology has led to an increase in the switching speed of the digital chip. As a result, there is a growing interest in the inductance associated with signal lines. Inductive coupling effects on interconnects is an emerging concern in high performance digital integrated circuits. Based on an RLC transmission line model, associated to each propagation mode, a new crosstalk noise model is proposed to evaluate both the capacitive and the inductive coupling. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…We will now compare these results with crosstalk voltages characteristics simulated from the reference distributed coupled-line system. Remark that the reference and the equivalent models are described in our previous works [6] [7]. For the electrical simulations, we use the electrical parameters we have determined for a 1GHz frequency on an upper level typical interconnect geometry.…”
Section: Spice Simulation Validationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We will now compare these results with crosstalk voltages characteristics simulated from the reference distributed coupled-line system. Remark that the reference and the equivalent models are described in our previous works [6] [7]. For the electrical simulations, we use the electrical parameters we have determined for a 1GHz frequency on an upper level typical interconnect geometry.…”
Section: Spice Simulation Validationsmentioning
confidence: 99%
“…In [7], we have shown that the crosstalk resulting to the total coupling (capacitive + inductive) could be written as the sum of the coupling effects. In Laplace domain, crosstalk voltage can be written as: …”
Section: Introductionmentioning
confidence: 99%
“…According to [10], capacitive and inductive coupling noise is additive under the low loss approximation, () however that the low loss approximation cannot always be assumed in modern integrated circuits. Therefore, additivity of the two noise sources cannot be assumed in modern integrated circuits.…”
Section: Additivity Of Capacitive and Inductive Coupling Noisementioning
confidence: 99%
“…Therefore, additivity of the two noise sources cannot be assumed in modern integrated circuits. By performing an analysis similar to [10], those regimes where additivity of capacitive and inductive coupling can be assumed, as illustrated in Fig. 3 for a two coupled line system, are established.…”
Section: Additivity Of Capacitive and Inductive Coupling Noisementioning
confidence: 99%
See 1 more Smart Citation